EVALUASI IMPLEMENTASI PROGRAM MAGANG INDUSTRI UNTUK PENGEMBANGAN KOMPETENSI TEKNIK OTOMASI INDUSTRI SMK MUHAMMADIYAH 2 CILEUNGSI - Gusti, Tika Sylviani; Maksum, Hasan; Novaliendry, Dony (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to evaluate the effectiveness of the industrial internship program implementation in the Industrial Automation Engineering Expertise Program at SMK Muhammadiyah 2 Cileungsi. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model to obtain a comprehensive overview of the suitability of objectives, implementation readiness, internship process, and student outcomes. This study used a mixed-approach with a total sampling technique involving 50 students in grades XI and XII, as well as qualitative informants consisting of supervising teachers, industrial supervisors, and the head of the expertise program. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using descriptive statistics and qualitative analysis using the Miles and Huberman model. The results indicate that the industrial internship implementation has not been fully effective in supporting the development of students' technical competencies. The main problem lies in the mismatch between student placement and Industrial Automation Engineering expertise, resulting in many students not engaging in relevant work activities such as PLC programming, wiring panels, instrumentation, pneumatics, and industrial control systems. Instead, some students are placed in non-technical jobs that do not contribute to the improvement of automation skills. Nevertheless, the internship program still has a positive impact on the development of soft skills such as discipline, communication, and adapting to work culture. The study concluded that internship effectiveness would increase if the placement system were improved through student competency mapping, alignment with industry needs, and expanding partnerships with companies with work units in the automation sector. ABSTRAK Penelitian ini bertujuan untuk mengevaluasi efektivitas implementasi program magang industri pada Program Keahlian Teknik Otomasi Industri SMK Muhammadiyah 2 Cileungsi. Evaluasi dilakukan menggunakan model CIPP (Context, Input, Process, Product) untuk memperoleh gambaran menyeluruh terkait kesesuaian tujuan, kesiapan pelaksanaan, proses magang, serta hasil yang dicapai siswa. Penelitian ini menggunakan pendekatan campuran dengan teknik total sampling yang melibatkan 50 siswa kelas XI dan XII, serta informan kualitatif yang terdiri dari guru pembimbing, pembimbing industri, dan kepala program keahlian. Data dikumpulkan melalui angket, wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan statistik deskriptif dan analisis kualitatif model Miles dan Huberman. Hasil penelitian menunjukkan bahwa pelaksanaan magang industri belum sepenuhnya efektif dalam mendukung pengembangan kompetensi teknis siswa. Permasalahan utama terletak pada ketidaksesuaian penempatan siswa dengan bidang keahlian Teknik Otomasi Industri, sehingga banyak siswa tidak terlibat dalam aktivitas kerja yang relevan seperti pemrograman PLC, wiring panel, instrumentasi, pneumatik, dan sistem kontrol industri. Sebaliknya, sebagian siswa ditempatkan pada pekerjaan non-teknis yang tidak berkontribusi pada peningkatan keterampilan otomasi. Meskipun demikian, program magang masih memberikan dampak positif pada pengembangan soft skills seperti kedisiplinan, komunikasi, dan adaptasi budaya kerja. Penelitian menyimpulkan bahwa efektivitas magang akan meningkat apabila sistem penempatan diperbaiki melalui pemetaan kompetensi siswa, penyelarasan kebutuhan industri, serta perluasan kemitraan dengan perusahaan yang memiliki unit kerja sesuai bidang otomasi.